Growth and Production of corn plants (Zea Mays) by providing organic matter and mulch types on marginal land - Hinarti, Wa Ode (Universitas 17 Agustus 1945 Samarinda, 2025)
Corn plants in Indonesia are the second staple food after rice. This study aims to determine the response of corn plants (Zea Mays L.) to the provision of organic materials and mulch on dry land in Muna Regency. The study was conducted in Wali Village, Watopute District, Muna Regency. The implementation of this study lasted for four months, starting from February 2011 to May 2011. This study was arranged based on a Randomized Block Design in a Factorial pattern with three replications as a group consisting of two factors. The first factor was the treatment of organic material dosage (P). The second factor was the treatment of mulch type (M). ANOVA test was conducted to determine the effect of treatment, if significant effect was continued with Duncan's Multiple Regression Test (DMRT) at a significance level of 0.05%. Observation variables include: Plant growth, and corn crop production. The results showed that the interaction between organic materials and mulch types had a significant effect on plant height. The application of organic materials had no significant effect on diameter. The highest production of dry shelled corn was produced in the treatment of providing organic materials at a dose of 15 tons haˉ¹, amounting to 4.08 tons haˉ¹ or an increase of 41.67% compared to without providing organic materials.